The Effect of Service Quality, Product Quality, and Price on Customer Loyalty with Customer Satisfaction as an Intervening Variable (Study at Tom Sushi Surabaya) - Bebyzanna Bella Faumara; Budi Prabowo; Rusdi Hidayat Nugroho; Indah Respati Kusumasari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research was conducted to examine the extent to which service quality, product quality, and price are able to shape customer loyalty, with customer satisfaction as the link, at Tom Sushi Surabaya. This research departs from the phenomenon of increasing Japanese culinary trends in Indonesia as well as the business need to keep customers loyal in the midst of fierce competition. Using a quantitative approach and purposive sampling technique of 100 respondents, the data was analyzed using the Partial Least Square (PLS) method. The research findings show that product quality and price have a positive and significant impact on customer satisfaction, while service quality does not show a significant influence. Customer loyalty was shown to be influenced by price and satisfaction level, but not directly by service or product quality. On the other hand, customer satisfaction plays an intermediary role in the relationship between product quality and price and loyalty, but not service quality.